Implementation of AI-Based Educational Games to Improve Early Reading Skills of Elementary School Students - Sukma Selfia Rianti; Evi Chamalah; Rida Fironika Kusumadewi; Stevanus Adrianto Passat (EduBase : Journal of Basic Education, 2025)
Objective: This study aims to test the effectiveness of implementing an Artificial Intelligence (AI)-based educational game in improving early reading skills among elementary school students. Novelty: The integration of AI-based educational games in early reading instruction is a relatively new approach in the context of elementary education in Indonesia, offering adaptive and interactive learning experiences tailored to students' needs. Methods: The study employed an experimental method with a pretest-posttest control group design. A total of 60 first-grade students from Taruna Mandiri Elementary School, Tangerang, were randomly assigned to two groups: an experimental group and a control group, each consisting of 30 students. The experimental group used AI-based educational games during reading instruction, while the control group used conventional teaching methods. The instrument used was an early reading ability test covering letter recognition, syllables, and simple word reading. Results: Data analysis revealed a statistically significant difference in posttest scores between the two groups. Students in the experimental group showed a markedly greater improvement in early reading skills compared to those in the control group. Conclusion: The use of AI-based educational games is proven to be effective in enhancing early reading abilities in elementary school students.